Thrombus in Transit through Patent Foramen Ovale. (30th September 2013) - Baydoun, Hassan; Barakat, Iskander; Hatem, Elie; Chalhoub, Michel; Mroueh, Ali
Abstract : A thrombus in transit through a patent foramen ovale (PFO) with impending paradoxical embolism is an extremely rare event. Due to its transient nature, it is unable to identify the thrombus, and most of the cases have been reported at autopsy. We are reporting a case of thrombus straddling the foramen ovale which was diagnosed by echocardiography and treated surgically. Through this personal case, an exhaustive review of the literature was performed. There were 88 cases reported. We concluded that there is no medical consensus about the best option for treatment. Nevertheless, surgery, which is associated with fewer complications of recurrent embolic events than those of thrombolysis and anticoagulation, appeared to be the best approach in patients who are not at a high surgical risk. Anticoagulant treatment appears to be an acceptable therapeutic alternative to surgery, particularly in patients with comorbidities who are at high surgical risk and for patients with small PFO. Thrombolysis is linked to the highest mortality, which could be explained by the severity of the patient's initial presentation. In conclusion, and after the cumulative effects of these case reports, we propose a diagram consisting of the use of the three therapeutic options in the different clinical scenarios.